Pengaruh Penggunaan Lembar Kerja Siswa (LKS) Terhadap Prestasi Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam - Ismaraidha, Ismaraidha (Al-Fikru: Jurnal Ilmiah, 2021)
This study aims to determine the effect of using Student Worksheets on student achievement in Islamic subjects. This study uses quantitative research methods using correlation techniques. The population as well as the sample in this study were all students of SMP Laut Dendang, totaling 40 students. Data collection techniques using interview techniques, questionnaires, and observations. Correlation calculation is done by testing the hypothesis with the Product Moment correlation formula. The results showed that there was a positive influence between the use of student worksheets and student achievement in Islamic subjects, this is indicated by the results of calculations where rcount= 0.719 while rtable= 0.302. This calculation also means that the teaching and learning process of teachers and students can make the most of the Student Worksheets so that student learning achievement will increase significantly.